QUALITY OF LIFE IN PATIENTS WITH PRIOR OSTEOPOROTIC VERTEBRAL FRACTURE - A. G. Solodovnikov; O. M. Lesnyak; O. V. Dobrovolskaya; K. Yu. Belova; Yu. A. Varavko; G. Sh. Golubev; V. A. Grebenshchikov; O. B. Ershova; E. G. Zotkin; S. N. Ivanov; A. Yu. Kochish; L. V. Menshikova; et al. (Научно-практическая ревматология)
Objective: to analyze the dynamics of quality of life (QOL) in patients with prior osteoporotic vertebral compression fracture during an 18-month follow-up study. Subjects and methods. The investigation enrolled 219 patients (mean age, 67.6 years) with vertebral fracture from seven centers of the Russian Federation. QOL was assessed four times using the EQ-5D (EuroQoL-5D) and TTO (Time Trade-Off) questionnaires during an 18-month prospective follow-up study. The work was done within the framework of the International Multicenter Study ICUROS (The International Costs and Utilities Related to Osteoporotic Fractures Study) organized by the International Osteoporosis Foundation (www.icuros.org).Results and discussion. The patients with vertebral compression fracture showed a statistically significant decrease in QOL throughout the follow-up period. Immediately after the fracture, there was a dramatic decrease in the total EQ-5D score, followed by its gradual increase. However, the emerging trend in QOL recovery proved to be unstable, and by the end of the 18th month, it was significantly lower than that before the fracture. On the contrary, the TTO questionnaire showed that QOL drastically decreased immediately after fracture, but at month 4 it reached the level that was before the fracture, and remained stable until the end of the follow-up period.Conclusion. The performed investigation enabled us to obtain data on QOL using the EQ-5D (QOL assessment from the social point of view) and TTO (individual QOL assessment) in the population of residents of the Russian Federation, in men and women aged 50 years and older with osteoporotic vertebral compression fracture.